The Influence of PAILKEM (Active, Innovative, Environmental, Creative, Effective and Interesting Learning) on the Literacy Understanding of Class I and Class II Students at SD Negeri 163 Palembang - Erikawati Erikawati; Dessy Wardiah; Djunaidi Djunaidi (International Journal of Social Science and Humanity, 2025)
The aim of this research is to evaluate the influence and effectiveness of the PAILKEM method (Active, Innovative, Environmentally Friendly, Creative, Effective, Interesting Learning) in improving the literacy understanding of class I and II students at SD Negeri 163 Palembang. The research method used was quasi-experimental with a pretest-posttest control group design. The sample consisted of two groups, namely the experimental group which was given learning using the PAILKEM method and the control group which used the conventional method. Data collection techniques include pretest, posttest, and questionnaire, which are analyzed using the N-Gain test, independent sample t-test, and homogeneity test. Research data includes primary data in the form of pre-test and post-test results as well as secondary data collected using a questionnaire to determine student responses to this method. The increase in posttest scores in the experimental group was significant compared to the control group. The t-test results show that there is a significant difference between the experimental and control groups, which means that the application of PAILKEM has a significant influence on increasing students' literacy understanding. This is reinforced by the results of the N-Gain test which meets the high criteria and meets the Indonesian KKTP. The student questionnaire also showed very good responses regarding various aspects of the PAILKEM dimensions. In conclusion, the PAILKEM method is effective and has a positive effect on the literacy understanding of grade I and II students and can be used as an innovative alternative in teaching literacy in elementary schools.